Zuo yike hongsede zhongzi - Dao zuguo zui xuyaode difang shenggen faya, kaihua, jieguo! - Ha Qiongwen,
'Become a red seedling - Strike root, sprout flower and bear seed in the places the motherland needs it most!'. Printno. 8085.2662 (7). With signature of the designer.